Formation of PT Bhanda Ghara Reksa logistics Indonesia's brand awareness through digital transformation - Siagian, Ade Indriani; Dewi, Evie Ariadne Shinta; Yustikasari, Yustikasari (Universitas Wiralodra, 2024)
This research aims to understand the reasons behind PT Bhanda Ghara Reksa Logistik Indonesia's digital transformation and analyze how the company builds brand awareness through digital transformation. The research methodology employed is qualitative, using a case study approach. Data collection involves in-depth interviews, observations, and literature review. The data analysis technique used is the interactive data analysis technique by Miles and Huberman, often referred to as the data flow model, consisting of data reduction, data display, and concluding. The research findings indicate that PT BGR LI's reasons for digital transformation are to optimize services to the public and stakeholders, enabling the formation of brand awareness and fostering trust among the public and stakeholders in PT BGR LI. The way PT BGR LI builds brand awareness through digital transformation is implemented through four forms of transformation: system and service transformation, product transformation, technological transformation, and organizational culture and human resources transformation.